PENDIDIKAN KARAKTER BERBASIS AL-QUR’AN DAN HADIS (STUDI ANALISIS KONSEPTUAL) - Khairah, Miftahul; Fadliatun Mutmainnah; Maidin, Muh. Sabir (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This research uses a qualitative research method with a library research approach. Data collection techniques were carried out through literature review studies by referring to relevant and recent reference sources. This research aims to analyse the relationship between character education and the Qur'an and Hadist. The operational definition of variables includes character education, the Qur'an, and Hadist. The results of this study are expected to contribute to the development of character education based on the values of the Qur'an and Hadist. Character education based on the Qur'an and Hadist is a strategic effort to build a generation that has a superior personality, noble character, and is oriented towards spiritual values. This article aims to analyse the concept of character education in the perspective of the Qur'an and Hadist and its implications for educational practices in the modern era. Using a qualitative approach through a literature study, this research reveals that core values such as honesty, responsibility, and compassion are at the core of character building according to Islamic teachings. The implications of this analysis show the importance of integrating these values in the education curriculum to create harmony between science and spiritual values.